Enhancing sustainability and energy conservation in Indian railway tunnels through innovative lighting control and predictive maintenance - Alagirisamy, Mukil; Shinde, Sagar; Nikumbh, Pranav; Jadhav, Karan; Jadhav, Nikita (International Journal of Innovative Research and Scientific Studies, 2025)
The proposed innovation presents an innovative method for optimizing energy consumption and maintenance in railway tunnel operations, responding to the urgent need for sustainable and cost-effective infrastructure. This solution utilizes advanced geofencing technology integrated with a powerful cloud-based automation platform to guarantee accurate control of tunnel illumination and infrastructure management. The technology optimizes illumination levels in real-time according to train location, speed, and movement patterns, thereby minimizing energy waste, substantially lowering operational costs, and improving safety standards. The cloud platform functions as a single hub for overseeing and administering the tunnel’s essential infrastructure, facilitating the seamless integration of real-time diagnostics, predictive maintenance algorithms, and automatic anomaly detection. In cases of system abnormalities, the platform enables swift remote intervention, hence ensuring system dependability and reducing downtime. This holistic strategy not only tackles the urgent operating issues of railway systems but also aligns with long-term sustainability objectives by fostering energy conservation and minimizing environmental impact. This breakthrough enhances operational efficiency and dependability, providing a transformative solution for contemporary railway networks and facilitating the development of greener, more intelligent transportation systems.